Alkaline Pulping of Red Meranti (Shorea selanica Blume) - Lukmandaru, Ganis; Setiaji, Fajar; Warahapsari, Ayu (Wood Research Journal, 2014)
The suitability for papermaking of red meranti (Shorea selanica Blume) wood for three alkaline pulping processes i.e soda, soda-anthraquinone (AQ), and kraft was studied. The ﬁber morphology and chemical properties were also examined. Cooks were made for 20% (as Na2O) activate alkali. The resulting pulp and paper properties were investigated. The basic density of red meranti was 0.42 g/cm3 and can be classified to be of medium density. The fibre proportion (67.14%) and fibre length (1.07 mm) of red meranti in this study were within the range of tropical hardwoods. The derived values for Runkel ratio, slender ratio, and flexibility coefficient were 0.54, 54.93, and 0.62, respectively. Furthermore, total extractives, lignin, and cellulose contents as well as solubility in 1% NaOH were 5.17%, 31.05%, 45.20%, and 26.02%, respectively. The alkaline pulps showed low kappa number (16~22) and reject level (0.5~1.5%) with the best results for screened yield (47.41%) being achieved in soda pulping. With regard to strength and optical properties of the paper hand-sheets, soda-AQ pulping showed the highest value in burst index (2.36 KPa m2/g), tear index (8.47 + 1.13 mNm2/g), and brightness (19.81%), whereas kraft pulping gave the best result in tensile index (28.39 Nm/g). The comparatively low values of yield and strength properties in kraft pulping might be due to overcooking in this experiment.